Implementasi Tujuan Intruksional Khusus di SDN Pasir Awi pada Era Pandemi Covid 19 - Magdalena, Ina; Salsabilla, Khalisa; Yanti, Tiara Dama; Annisa, Tiara Nur (MASALIQ, 2022)
This study aims to determine the implementation of special instructional objectives at PASIR AWI Elementary School in the era of the COVID-19 pandemic since the Covid 19 outbreak. All learning activities that were previously face-to-face have become online learning, including at PASIR AWI Elementary School. In this study, the interview method was conducted with one of the primary school teachers. The interview was conducted face-to-face by applying health protocols, such as keeping a distance and using masks. The results showed that online learning or being brave was less effective for students because there were many parents who could not invited to cooperated.